Afferent baroreflex failure in familial dysautonomia - Norcliffe-Kaufmann, Lucy (American Academy of Neurology, 2010)
BACKGROUND: Familial dysautonomia (FD) is due to a genetic deficiency of the protein IKAP, which affects development of peripheral neurons. Patients with FD display complex abnormalities of the baroreflex of unknown cause. METHODS: To test the hypothesis that the autonomic phenotype of FD is due to selective impairment of afferent baroreceptor input, we examined the autonomic and neuroendocrine responses triggered by stimuli that either engage (postural changes) or bypass (cognitive/emotional) afferent baroreflex pathways in 50 patients with FD and compared them to those of normal subjects and to those of patients with pure autonomic failure (PAF), a disorder with selective impairment of efferent autonomic neurons. RESULTS: During upright tilt, in patients with FD and in patients with PAF blood pressure fell markedly but the heart rate increased in PAF and decreased in FD. Plasma norepinephrine levels failed to increase in both groups. Vasopressin levels increased appropriately in patients with PAF but failed to increase in patients with FD. Head-down tilt increased blood pressure in both groups but increased heart rate only in patients with FD. Mental stress evoked a marked increase in blood pressure and heart rate in patients with FD but little change in those with PAF. CONCLUSION: The failure to modulate sympathetic activity and to release vasopressin by baroreflex-mediated stimuli together with marked sympathetic activation during cognitive tasks indicate selective failure of baroreceptor afference. These findings indicate that IKAP is critical for the development of afferent baroreflex pathways and has therapeutic implications in the management of these patients. GLOSSARY: FD: = familial dysautonomia; FVR: = forearm vascular resistance; PAF: = pure autonomic failure.